Mapping and Visualizing Bullwhip Effect Research with a Bibliometric Analysis - Lemadi, Gayuh; Prasetio, Dian Eko Adi; Lutfiani, Lutfiani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The Bullwhip Effect occurs due to demand information distortion from the retail level up to suppliers, ultimately resulting in inefficiencies and losses within the supply chain. The purpose of this paper is to present a bibliometric literature review related to the Bullwhip Effect as a key issue in supply chain management. Article data were collected from the Google Scholar database spanning from 1997 to 2025, yielding a total of 1,000 articles. A significant portion of the research originates from Indonesia, with findings indicating that most articles are indexed in SINTA 4, while no Scopus-indexed publications were found between 2015 and 2025. Reference management was conducted using the Publish or Perish and Mendeley software tools. The bibliometric analysis was carried out in five stages: (1) Initial keyword selection, (2) Initial search results, (3) Filtering of search results, (4) Compilation of preliminary statistics, and (5) Data analysis. The three most frequently co-occurring keywords with “Bullwhip Effect” were supply chain, impact, and model. Further data classification was performed using VOSviewer software, which was employed to identify the most frequently cited publishers and to map research opportunities related to supply chain studies, particularly those aimed at mitigating the Bullwhip Effect.